2023
DOI: 10.3390/molecules28062734
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and In Vitro Antioxidant Activity and Anti-Acetylcholinesterase Activity of Essential Oils from Tadehagi triquetrum (L.) Ohashi

Abstract: The present study aimed to determine the chemical compositions of essential oils (EOs) from Tadehagi triquetrum (L.) Ohashi and evaluate their antioxidant and anti-cholinesterase activity under the comprehensive influence of chemical components. The essential oils were extracted from T. triquetrum (L.) Ohashi by hydrodistillation. A total of 58 organic compounds were identified by GC-FID and GC-MS analysis. The major components of T. triquetrum (L.) Ohashi EOs were identified as palmitic acid (22.46%), 1-Octen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Prior research has shown the IC 50 values of A. annua and O. vulgare to be at 5.97 ± 0.51 mg/mL and 7.35 ± 0.30 mg/mL, respectively [ 55 , 56 ], suggesting their ABTS •+ free radical-scavenging activities are inferior to our essential oil. Nonetheless, other essential oils, such as S. rhombifolia and T. triquetrum , have demonstrated superior ABTS •+ -scavenging activities with IC 50 values of 1.47 ± 0.01 mg/mL [ 53 ] and 2.12 ± 0.05 mg/mL [ 54 ], indicating a more potent ability to neutralize free radicals. In the preceding experiments, the ABTS assay consistently demonstrated superior sensitivity in detecting free radical-scavenging activity compared to the DPPH assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research has shown the IC 50 values of A. annua and O. vulgare to be at 5.97 ± 0.51 mg/mL and 7.35 ± 0.30 mg/mL, respectively [ 55 , 56 ], suggesting their ABTS •+ free radical-scavenging activities are inferior to our essential oil. Nonetheless, other essential oils, such as S. rhombifolia and T. triquetrum , have demonstrated superior ABTS •+ -scavenging activities with IC 50 values of 1.47 ± 0.01 mg/mL [ 53 ] and 2.12 ± 0.05 mg/mL [ 54 ], indicating a more potent ability to neutralize free radicals. In the preceding experiments, the ABTS assay consistently demonstrated superior sensitivity in detecting free radical-scavenging activity compared to the DPPH assay.…”
Section: Resultsmentioning
confidence: 99%
“…The DPPH radical accepts electrons or hydrogen radicals from the donor compound and exhibits a strong absorption band at 515-520 nm [52]. At the highest concentration (10 mg/mL), the antioxidant activity of essential oil was 31.98%, whose potency seems weaker than those obtained from essential oils of other species [45,53,54].…”
Section: Antioxidant Activity Evaluationmentioning
confidence: 99%
“…The percentages of inhibition of the oils were compared with the inhibition induced by the 1 mM Trolox solution. The total antioxidant capacity expressed in mg ET/mL of oil was calculated according to the equation proposed by [60,61]. Essential oils were tested without dilution.…”
Section: Antioxidant Potentialmentioning
confidence: 99%